Chemical composition of tourmaline from the Asarcık Pb–Zn–Cu ± U deposit, Şebinkarahisar, Turkey - Yavuz, F.; Fuchs, Y.; Karakaya, N.; Karakaya, M. C. (Springer Science and Business Media LLC, 2008)
Abundant tourmaline, commonly as rosettes up to 1.5 cm in diameter, is present in the Upper Cretaceous Asarcik granitoid (Sebinkarahisar), Northeastern Turkey. The tourmalines also occur in quartz–tourmaline veins up to 4 m thick that cut the Asarcik granitoid. This granitoid was emplaced in the eastern Pontide Metallogenic Belt, where accompanying tourmalines are found in close association with a vein-type, uranium-bearing Pb–Zn–Cu deposit. Tourmaline crystals are generally optically zoned from core to rim with a bluish green core. Electron-microprobe studies show that tourmalines from the Asarcik granitoid and quartz–tourmaline veins display mainly dravite–schorl solid solutions with a tendency to schorl compositions. The tourmaline from the Asarcik granitoid has Fe/(Fe + Mg) ratios from 0.28 to 0.69 (mean = 0.52) and Na/(Na + Ca) ratios from 0.57 to 0.93 (mean = 0.76). In contrast, tourmaline in the quartz–tourmaline veins has Fe/(Fe + Mg) ratio from 0.14 to 0.92 (mean = 0.59) and Na/(Na + Ca) ratio from 0.78 to 1.00 (mean = 0.96). Tourmaline in the veins has a more alkali-deficient trend than that in the granitoid. Substitution mechanisms for the chemical evolution of tourmalines at Asarcik are the MgFe−1, (Fe2+Fe3+)(MgAl)−1, □Al(NaR)−1, AlOR2+−1(OH)−1, □Al2ONa−1R2+−2(OH)−1, Ca0.5□0.5Na−1, CaMg2□−1Al−2, CaMgO□−1Al−1(OH)−1, CaMg3OH□−1Al−3O−1, CaMgNa−1Al−1, CaONa(OH)−1, CaMg2OHNa−1Al−2O−1, CaMg2□−1Al−2, and CaMg3OH□−1Al−3O−1 exchange vectors. Chemical zoning in the tourmalines is consistent with these substitutions. Stoichiometric calculations of electron-microprobe data in the Asarcik granitoid suggest a relatively oxidizing environment during tourmaline crystallization.